Participant Satisfaction Mediation: The Impact of Service Quality and Trust on Loyalty in Mobile JKN Participants of BPJS Kesehatan Madiun Branch - Anung Budiranto; Eko Budi Satoto; Trias Setyowati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of service quality and trust on the loyalty of participants of the Mobile JKN application BPJS Kesehatan Madiun Branch, with participant satisfaction as a mediation variable. The research method uses a quantitative approach through a questionnaire survey to Mobile JKN participants. The results of the study show that service quality including usage efficiency, system reliability, feature responsiveness, and personal data protection have a positive and significant effect on participant loyalty, both directly and through participant satisfaction as a mediation variable. Participants' trust in the integrity, transparency, and competence of service managers also has a strong effect on loyalty, where participant satisfaction mediates the relationship significantly. The findings prove that participant satisfaction is the main bridge that connects service quality and trust with the loyalty of Mobile JKN application users. The recommendations from this study are the importance of increasing digital feature innovation, transparency, and participant education to strengthen the satisfaction and loyalty of BPJS Kesehatan digital health service users